อิทธิพลแบบปรับของประเภทของครูอาชีวศึกษาและบรรยากาศองค์กร ตามการรับรู้ที่มีต่อโมเดลเชิงสาเหตุของความต้องการจำเป็นระดับบุคคล ในการนำไปสู่ความเป็นองค์กรแห่งการเรียนรู้ - ฉัตรชนก สายสุวรรณ (จุฬาลงกรณ์มหาวิทยาลัย, 2005)
To (1) examine the levels of individual needs of vocational teachers in the Office of Vocational Education Commission in Thailand on becoming learning organization, (2) establish and validate the causal model of indiviual needs on becoming learning organization (3) investigate the moderating effects of types of vacational teachers and perceived organizational climate on the causal model of individual needs on becoming learning organization. This research used survey method. Subjects for the study were vocational teachers from the Office of Vocational Education Commission in Thailand. Data were collected by means of questionnaires and analyzed employing LISREL. The research findings were summarized follows (1) Individual input needs, process needs and output needs of vocational teachers in the Office of Vocational Education Commission in Thailand on becoming learning organization was a high level. Individual process needs was higher than output needs and input needs. The factors strongly influencing of individual input needs, process needs and output needs were personal mastery, technology application and professional development. (2) The development causal model of individual needs on becoming learning organization was also well fitted with the imperical data. (chi-square = 4.61, df = 14, p = .99, GFI = 1.00, AGFI = .99) and they could explain 68 and 74 percent of individual process needs and output needs. (3) The moderating effects of type of vocational teachers and percieved organizational climate on the causal model of individual needs on becoming learning organization showed that the model was invariant in terms of the model form and the matrix of causal effected between endogenous and exogenous latent variables